D-Convergence of Runge-Kutta Methods for Stiff Delay Differential Equations (Journal of Computational Mathematics, 2001)
This paper is concerned with the numerical solution of delay differential equations (DDEs). We focus on the error behaviour of Runge-Kutta methods for stiff DDEs. We investigate D-convergence properties of algebraically stable Runge-Kutta methods with three kinds of interpolation procedures.
Keywords: Delay Differential equations; Runge-Kutta methods; D-convergence.